Experimentar a Poesia: A moderna Ars Portica de Sophia de Mello Breyner Andresen - Costa, Leila Aguiar [UNESP] (My University, 2005)
The present article attempts to appraise the poetics of Sophia de Mello Breyner Andresen looking into her Ars Poética poems. It will be shown how, for the author, the modern isotopy of a being-in-the-world acts as one of the writing engines and, consequently, points to a reciprocal implication between Work and Otherness, between things and experience.
To experience poetry: The modern Ars Poetic of Sophia de Mello Breyner Andresen
Keywords: Being-in-the-world; Hearing; Look; Perception; Relation; Subject-object